Assessment of the Ecological Status of Rongjiang Estuary (China) Under Human Pressure, Using Biotic Indices Based on Benthic Macroinvertebrates - Li, Yafang; Wang, Lianggen; Ning, Jiajia; Xu, Lei; Huang, Delian; Liu, Shuangshuang; Du, Feiyan (Frontiers in Environmental Science, 2021)
Rongjiang River, the second largest river system in Guangdong Province, flows through the main urban areas of Jieyang and Shantou cities before reaching the South China Sea. Human activities in the surrounding area pose significant threats to this aquatic ecosystem. The ecological status (ES) of the benthic ecosystem of the Rongjiang River estuary has not yet been conducted using indices based on the macrobenthic fauna, which is important for evaluating environmental health. Here, we used four biotic indices (the AZTI’s Marine Biotic Index (AMBI) and Multivariate AZTI’s Marine Biotic Index (M-AMBI), and taxonomic distinctness indices (average taxonomic distinctness Δ+ and variations in taxonomic distinctness Λ+) to appraise the current ES of benthic communities in Rongjiang estuary. Samples were taken from 11 sampling sites located in six general regions: western aquaculture zones, aquaculture zones, Hanjiang River water channel, Shantou City, Shantou Port, and near the ocean. The benthic ecosystem of this estuary is greatly disturbed: the ES of the aquaculture zones and the sites near the Hanjiang River water channel, Shantou City, and close to the ocean was poorer compared with that of other areas; ES was also poorer in winter than in summer. Generalized linear models revealed that Shannon-Wiener index was negatively correlated with dissolved inorganic nitrogen (P < 0.01), M-AMBI was negatively correlated with temperature and dissolved inorganic nitrogen (P < 0.05 and P < 0.01, respectively), and Λ+ was negatively correlated with pH (P < 0.05). The AMBI, M-AMBI, Δ+, and Λ+ indices were suitable for assessing the ES of the benthic ecosystem in an anthropogenically disturbed estuary.